2021
DOI: 10.1620/tjem.254.63
|View full text |Cite
|
Sign up to set email alerts
|

<i>miR-4270</i> Modulates the Irradiation-Sensitivity of Nasopharyngeal Carcinoma Cells through Modulation of p53 <i>in Vivo</i>

Abstract: The lowered sensitivity to irradiation considerably impacted on the prognosis of nasopharyngeal carcinoma treatments. This study aimed to explore the functions of miR-4270 in nasopharyngeal carcinoma. Bioinformatic analysis was performed online accessing GSE139164 dataset to screen the top 30 differential microRNAs in nasopharyngeal carcinoma patients with radio-sensitivity. Cancer cell lines, 6-10B and 5-8F, were cultured and measured for expression of miR-4270 and TP53 (the gene of the tumor suppressor prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Wang and coworkers [ 8 ] have displayed that the inhibition of miR-4270 reduces cell proliferation and apoptosis by inactivating NOTCH signaling pathway in Sertoli-cell-only syndrome patients. Moreover, Hao et al [ 17 ] have shown that miR-4270 directly targets P53 gene in the human neural progenitor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Wang and coworkers [ 8 ] have displayed that the inhibition of miR-4270 reduces cell proliferation and apoptosis by inactivating NOTCH signaling pathway in Sertoli-cell-only syndrome patients. Moreover, Hao et al [ 17 ] have shown that miR-4270 directly targets P53 gene in the human neural progenitor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Hao et al. reported that the levels of miR-4270 modulate the irradiation-sensitivity of nasopharyngeal carcinoma cells through modulation of p53 in vivo ( 46 ). Collectively, these results suggest that different levels of miR-4270 expression may be associated with different cancers and that miR-4270 likely has different functions.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, other studies have shown that circulating miR-4270 displays upregulated levels in metastatic gastric cancer and breast cancer patients, with the potential use of miR-4270 as a diagnostic or prognostic biomarker (44,45). Hao et al reported that the levels of miR-4270 modulate the irradiation-sensitivity of nasopharyngeal carcinoma cells through modulation of p53 in vivo (46). Collectively, these results suggest that different levels of miR-4270 expression may be associated with different cancers and that miR-4270 likely has different functions.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of a TSG, a Pin2 telomeric repeat factor 1-interacting telomerase inhibitor 1 ( PinX1 ), was found to activate the TP53/miRNA-200 axis, which in turn suppressed the EMT of CSC in NPC [ 133 ]. A recent study also demonstrated that the upregulation of miR-4270 in NPC has inhibited TP53 signalling [ 236 ]. In addition, cyclooxygenase-2 (COX-2)’s interaction with TP53 has been known to induce chemoresistance by inhibiting chemotherapeutic-induced cellular senescence [ 132 ].…”
Section: Molecular Aberrations Exploitation In Npc For Precision Medi...mentioning
confidence: 99%